POLA AGROFORESTRI DI DESA KOKOLEH I KABUPATEN MINAHASA UTARA PROPINSI SULAWESI UTARA - Fermi Basir; Hengki D. Walangitan; Reynold P. Kainde (Universitas Sam Ratulangi, 2018)
ABSTRACT The aim of the study was to describe the agroforestry patterns applied by farmers in Kokoleh I Village from November to December 2017. The method used was purposive sampling method using a sample plot measuring 20 m x 20 m. The variables observed were plant species and the number of individuals of each species. Data analyzed descriptively are presented in tabular form. The results showed that agroforestry patterns in Kokoleh I village were dominated by nantu and cempaka species for tree, coconut and nutmeg components for plantation, durian and langsat for fruit crops while seasonal crops were dominated by maize and peanuts. Â Keywords: Agroforestry Pattern, Kokoleh Village I